IDENTIFIKASI LITERASI SAINS SISWA KELAS XI SMA YPK DIASPORA KOTARAJA - Hanida Listiani; Nurbaya Nurbaya; Suriyah Satar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Scientific literacy is one of the skills that must be possessed in the 21st Century. The aim of this research is to identify the scientific literacy abilities of class XI students at SMA YPK Diaspora Kotaraja, Papua. This research uses a quantitative descriptive method to describe the initial scientific literacy abilities of YPK Diaspora Kotaraja High School students. The population used in this research were all class XI students of SMA YPK Diaspora Kotaraja. The sample in this study consisted of 30 students from class XI using a random cluster sampling technique (cluster sampling). Quantitative data in this research was obtained using the NoSLiT test instrument. The data obtained was then analyzed descriptively. The research results show that the scientific literacy abilities of YPK Diaspora Kotaraja High School students are in the low category. Based on these results, it is necessary to consistently apply scientific literacy in learning so that 21st century skills can be improved and become the foundation for students to build the nation in the future.